2012
DOI: 10.1590/s0100-879x2012007500060
|View full text |Cite
|
Sign up to set email alerts
|

Tissue transglutaminase (TG2) activity regulates osteoblast differentiation and mineralization in the SAOS-2 cell line

Abstract: Tissue transglutaminase (type II, TG2) has long been postulated to directly promote skeletal matrix calcification and play an important role in ossification. However, limited information is available on the expression, function and modulating mechanism of TG2 during osteoblast differentiation and mineralization. To address these issues, we cultured the well-established human osteosarcoma cell line SAOS-2 with osteo-inductive conditioned medium and set up three time points (culture days 4, 7, and 14) to represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…Furthermore, inhibition of TGM2 activity in the cultures by CYS significantly attenuated mechanical load-induced ALP activity ( Figure 5). The results are proportionally consistent with a previous study that TGM2 is involved in the initiation and regulation of the mineralization processes in osteosarcoma cell line SAOS-2 (40). Based on the above findings, it could be reasonably inferred that centrifugal force induces osteogenic differentiation of human ligamentum flavum cells possibly via TGM2-dependent mechanism.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, inhibition of TGM2 activity in the cultures by CYS significantly attenuated mechanical load-induced ALP activity ( Figure 5). The results are proportionally consistent with a previous study that TGM2 is involved in the initiation and regulation of the mineralization processes in osteosarcoma cell line SAOS-2 (40). Based on the above findings, it could be reasonably inferred that centrifugal force induces osteogenic differentiation of human ligamentum flavum cells possibly via TGM2-dependent mechanism.…”
Section: Discussionsupporting
confidence: 92%
“…Yin et al demonstrated that TGM2 gene expression and enzyme activity were upregulated during SAOS-2 osteoblast differentiation and mineralization. Inhibition of TGM activity significantly decreased osteocalcin (OC) and collagen-I gene expression, and ALP activity (40). In the present study, mechanical load significantly induced TGM2 gene expression and enzyme activity in human ligamentum flavum cells.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…51 Osteoblasts and osteoblastic cell lines have been reported to express both fXIIIA and tissue transglutaminase 2 (TG2). 52,53 Despite the local expression differences in crucial osteologic effectors observed in fXIIIA 2/2 mice, no overt skeletal abnormalities have been reported for fXIIIA 2/2 mice. Additionally, studies have reported that baseline skeletal properties of TG2-deficient mice are unaltered.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in matrix stiffness as a result of AGE formation and transglutaminase 2 activation may modify the niche and hence promote nontenocyte differentiation of stem cells in tendons. 64,65 In this regard, transglutaminase 2 was reported to regulate osteoblast differentiation in vitro 101 and to mediate the activation of the β-catenin signaling pathway which is central in vascular calcification. 102 Proteoglycans are key regulators of tendon function and are responsible for cell migration, differentiation, collagen fibril assembly, and fiber sliding.…”
Section: Erroneous Stem Cell Differentiationmentioning
confidence: 99%